Cannabinoid receptor‐2 agonist inhibits macrophage induced EMT in non‐small cell lung cancer by downregulation of EGFR pathway. Issue 12 (6th January 2016) - Ravi, Janani; Elbaz, Mohamad; Wani, Nissar A.; Nasser, Mohd W.; Ganju, Ramesh K.
Abstract : JWH‐015, a cannabinoid receptor 2 (CB2) agonist has tumor regressive property in various cancer types. However, the underlying mechanism by which it acts in lung cancer is still unknown. Tumor associated macrophage (TAM) intensity has positive correlation with tumor progression. Also, macrophages recruited at the tumor site promote tumor growth by enhancing epithelial to mesenchymal (EMT) progression. In this study, we analyzed the role of JWH‐015 on EMT and macrophage infiltration by regulation of EGFR signaling. JWH‐015 inhibited EMT in NSCLC cells A549 and also reversed the mesenchymal nature of CALU‐1 cells by downregulation of EGFR signaling targets like ERK and STAT3. Also, in vitro co‐culture experiments of A549 with M2 polarized macrophages provided evidence that JWH‐015 decreased migratory and invasive abilities which was proved by reduced expression of FAK, VCAM1, and MMP2. Furthermore, it decreased macrophage induced EMT in A549 by attenuating the mesenchymal character by downregulating EGFR and its targets. These results were confirmed in an in vivo subcutaneous syngenic mouse model where JWH‐015 blocks tumor growth and also inhibits macrophage recruitment and EMT at the tumor site which was regulated by EGFR pathway. Finally, JWH‐015 reduced lung tumor lesions in an in vivo tumorigenicity mouse model. These data confer the impact of this cannabinoid on anti‐proliferative and anti‐tumorigenic effects, thus enhancing our understanding of its therapeutic efficacy in NSCLC. Our findings open new avenues for cannabinoid receptor CB2 agonist‐JWH‐015 as a novel and potential therapeutic target based on EGFR downregulation mechanisms in NSCLC. © 2016 Wiley Periodicals, Inc.